When should video and EMG be added to urodynamics in children with lower urinary tract dysfunction and is this justified by the evidence? ICI‐RS 2014. Issue 2 (February 2016) - Anding, Ralf; Smith, Phillip; de Jong, Tom; Constantinou, Christos; Cardozo, Linda; Rosier, Peter
Abstract : Aims: An ICI‐RS Think Tank in 2014 discussed and evaluated the evidence for adding video and EMG to urodynamics (UDS) in children and also highlighted evidence gaps, with the aim of recommending further clinical and research protocols. Methods: A systematic analysis of the relevant literature for both X‐ray (video) studies and electromyography, in combination with UDS in children with lower urinary tract dysfunction (LUTD), is summarized in this manuscript. The technical aspects are also critically reviewed. Results: The body of evidence for the addition of X‐ray (video) to filling and voiding cystometry and the evidence for the addition of pelvic muscle surface electromyography to urodynamics is scanty and insufficient. Standards are poor and variable so uncontrolled expert opinion dominates practice. Conclusions: The Think Tank has recommended that standardized ALARA ("As Low As Reasonably Achievable") principles should be adopted for video‐urodynamics in children. The risk–benefit balance of X‐ray exposure needs to be better evaluated and defined. Evaluation of images should be standardized and the association with pressure changes better analyzed and reported. Children's pelvic muscle surface electromyography technique should be standardized, technically improved, and its diagnostic relevance should be better evaluated. Neurourol. Urodynam. 35:331–335, 2016 . © 2016 Wiley Periodicals, Inc.